Markers of hepatitis E among the population of the Greater Sochi and in monkeys of the Adler primate center - L. I. Korzaia; V. V. Keburia; D. I. Dogadov; B. A. Lapin; K. K. Kyuregyan; M. I. Mikhailov (Вопросы вирусологии, 2016)
Serum from humans (n = 646) and monkeys (n = 1867) collected during the period 1999-2013 was tested by enzyme immunoassay. Anti-HEV IgG was detected significantly more frequently (P ≥ 0.001) in rhesus macaques (Macaca mulatta) - 45.1 ± 1.6% (n = 1001) than in cynomolgus macaques (M. fascicularis) 16.2 ± 1.8% (n = 426). Single seropositive individuals were found among M. nemestrina - 4.0±2.8% (n = 50). Anti-HEV was not detected in the sera of green monkeys (Chlorocebus aethiops) - n = 162, Papio hamadryas (n = 124), and Papio anubis - n = 104. The presence of the anti-HEV IgM indicating the cases of fresh infection in Macaca mulatta - 2.1 ± 0.5% (n = 717) and M. fascicularis - 3.5 ± 1.3% (n = 266) is of great significance. The overall frequency of detection of the anti-HEV IgG among the staff of the Adler Primate Center - 6.8 ± 2.3% (n = 118) was significantly lower (P ≤ 0.001) than among the population of the Greater Sochi - 15.9% ± 1.6 (n = 528). It is important that only in patients of medical institutions (clinic, hospital, cancer center), anti-HEV IgM were detected (2.7-11.8%) along with anti-HEV IgG (15-23.5%), thereby indicating the presence of acute cases of HEV infection among this population. HEV RNA was not detected in the serum of anti-HEV IgM-positive people and monkeys. Seroepidemiological data do not confirm the assumption on the ability of seropositive monkeys of Macaca genus to be a natural reservoir of HEV infection for humans.